The Effect of Crown Ferrule Designs on Fracture Resistance of Endodontically Treated Teeth Restored with Fibre Posts, Composite Cores, And Crowns: An In-Vitro Study - Yadav, Antra; Agarwal, Abhinay; Yadav, Jyoti; Singh, Toshika; Singh, Jaya; Gupta, Sheersh (Journal of Neonatal Surgery, 2025)
Objective: This study aimed to evaluate effect of crown ferrule designs on fracture-resistance of restored endodontically treated teeth with fiber posts, cores, and crowns. Methods: Fifty six maxillary Central incisor were treated endodontically and divided into 4 groups with 14 teeth each; Group 1 with no ferrule (0FR); Group 2 with 2 mm circumferential ferrule (2FR); Group 3 with ferrule in labial, mesial and palatal side (2FR-LaMPa); Group 4 with ferrule in labial and palatal region(2FR-LaPA). All teeth were then restored with fiber-posts, composite cores and metal crowns. The samples were then subjected to load until failure occurred. Data were analyzed through one way analysis of variance and Tukey tests. Results: Significant differences were found between each study group and the control group. The study found that specimens with tooth preparations containing axial walls had significant more fracture-resistance compared to those from the 0FR group. Additionally, teeth with complete ferrule showed inferior fracture-resistance, possibly due to a smaller adhesive area for core built-up compared to teeth with interrupted ferrule, having larger bonding surface areas. Conclusion: The fracture-resistance of restored endodontically treated teeth with incomplete crown ferrules may be influenced by the location of these ferrules.